Diseño de un Polideportivo en el sector Monte Sinaí con estilo Brutalista - Mañay Zamora, Pablo Javier (2023)
This project proposes the design of a Brutalist-style Sports Center that is located in the Monte Sinai sector, northwest of the city of Guayaquil, this idea arises due to the lack of spaces dedicated to sports with the objective of providing inhabitants of that sector the opportunity to carry out different sports activities in a safe space. The sports center would have a tennis court, volleyball court, soccer field, and basketball court, as well as several outdoor areas that will function as spaces for recreation and relaxation. These areas will have concrete sidewalks where people can walk, run or carry out their sports activities with motivation and calm, reducing vehicular accidents that, in the absence of a Sports Center, play games on public roads, causing a traffic accident or causing road congestion............